Development of exposed rapid thermocouple for internal fluid temperature testing under pressure. (5th November 2022) - Zhang, Yin; Li, Xiaoran; Li, Chengyi; Wu, Weifeng; Wang, Jiangfeng
Highlights: A novel exposed thermocouple with multi-bended channels is designed for transient internal fluid temperature tests and can avoid the leakage of the internal fluid under 2 MPa, 200 °C. The thermocouple has the ability to detect transient temperature change with extremely fast response time of 1.74 ms. The model shows that the heat conduction error △ T s could be neglected in this case. The thermal inertia error △ T d caused by lag was the main error of thermal error caused by a thermocouple placed in a flow field. The average error of the whole exposed thermocouple was 0.32 K, which was 36 % lower than that in the referred literature. Abstract: Accurate measurement of transient temperature is essential for a variety of internal fluid temperature testing under pressure conditions. Casing thermocouples are widely applied because of its excellent sealing performance. However, the response of temperature change delays because of the heat transfer resistance through the protective casing. Traditional exposed thermocouples usually have fast response but need improvements in sealing performance. This paper presented a novel exposed thermocouple for transient internal fluid temperature tests under pressure conditions. Multi-bended channels filled with solid gum were designed to ensure sealing performance under 2 MPa, 200 °C. Fitted equation of its E-T curve was obtained by experiments with the response time of 1.74 ms. The thermodynamic model was established to estimate the performance of the thermocouple. It showed that the heat conduction error could be neglected in this case, thus reducing the influence of the rod effect. The testing of dynamic error under flash evaporation showed that the average error of the whole exposed thermocouple was 0.32 K, which was 36 % lower than that in the literature. Such satisfactory performance makes the novel exposed thermocouple competitive in internal fluid temperature testing of a rapidly changing transient temperature field.